2016
DOI: 10.1007/s00394-016-1209-x
|View full text |Cite
|
Sign up to set email alerts
|

A specific dose of grape seed-derived proanthocyanidins to inhibit body weight gain limits food intake and increases energy expenditure in rats

Abstract: GSPE at a dose of 0.5 g/kg can reduce body weight by limiting food intake and activating energy expenditure in subcutaneous adipose tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 36 publications
6
60
0
1
Order By: Relevance
“…We have previously reported that flavanols, a type of polyphenol found in abundance in grape seed proanthocyanidin extract (GSPE), have a modulatory effect on food intake. We described a dose that inhibited food intake and stimulated energy expenditure; this dose inhibited body weight gain by 60% after two eight-day periods of treatment [14]. Previously, we have shown that GSPE produces a lipolytic effect, which contributed to the effects on body weight in this study [12,15,16].…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…We have previously reported that flavanols, a type of polyphenol found in abundance in grape seed proanthocyanidin extract (GSPE), have a modulatory effect on food intake. We described a dose that inhibited food intake and stimulated energy expenditure; this dose inhibited body weight gain by 60% after two eight-day periods of treatment [14]. Previously, we have shown that GSPE produces a lipolytic effect, which contributed to the effects on body weight in this study [12,15,16].…”
Section: Introductionmentioning
confidence: 72%
“…Afterwards, we showed that a specific dose is needed to ensure a significant chronic effect on body weight control [14]. We now describe in deeper detail several aspects that should be taken into account if a GSPE treatment is to be effective.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations